Pentingnya Penanaman Nilai-Nilai Budaya Lokal dalam Keluarga di Era Global - Sri Sudarsih (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2019)
A global era whose existence cannot be denied brings logical consequences on every line of human life. Therefore, Javanese culture which has fundamental values is very relevant to study its relation to this global era. This research is a study in the field of philosophy related to Javanese cultural values. The method used by researchers is description and interpretation. One of the Javanese culture is the attitude of the Javanese people, namely the attitude of rila (sincere), temen (keep promises), watak (patience), and budi luhur (noble virtue) has a fundamental value meaning. These values becomes a parameter of one’s quality. The quality of one’s goodness can be measured by his practice of these values. These fundamental values are important to be realized in family life in this global era.